Cognitive Impairment and Neurogenotoxic Effects in Rats Exposed to Low-Intensity Microwave Radiation. (May 2015) - Deshmukh, Pravin Suryakantrao; Nasare, Namita; Megha, Kanu; Banerjee, Basu Dev; Ahmed, Rafat Sultana; Singh, Digvijay; Abegaonkar, Mahesh Pandurang; Tripathi, Ashok Kumar; Mediratta, Pramod Kumari
The health hazard of microwave radiation (MWR) has become a recent subject of interest as a result of the enormous increase in mobile phone usage. The present study aimed to investigate the effects of chronic low-intensity microwave exposure on cognitive function, heat shock protein 70 (HSP70), and DNA damage in rat brain. Experiments were performed on male Fischer rats exposed to MWR for 180 days at 3 different frequencies, namely, 900, 1800 MHz, and 2450 MHz. Animals were divided into 4 groups: group I: sham exposed; group II: exposed to MWR at 900 MHz, specific absorption rate (SAR) 5.953 × 10 −4 W/kg; group III: exposed to 1800 MHz, SAR 5.835×10 −4 W/kg; and group IV: exposed to 2450 MHz, SAR 6.672 × 10 −4 W/kg. All the rats were tested for cognitive function at the end of the exposure period and were subsequently sacrificed to collect brain. Level of HSP70 was estimated by enzyme-linked immunotarget assay and DNA damage was assessed using alkaline comet assay in all the groups. The results showed declined cognitive function, elevated HSP70 level, and DNA damage in the brain of microwave-exposed animals. The results indicated that, chronic low-intensity microwave exposure in the frequency range of 900 to 2450 MHz may cause hazardous effects on the brain.